From refugees to employees a comparison of the labour market entegration of Syrian refugees in Turkey and Germany - Kunzendorf, Laura (İstanbul Bilgi Üniversitesi, 2019)
Germany and Turkey, the two European states hosting the largest number of Syrian refugees, are faced with the challenge to integrate these refugees into their labour markets on the long-term. However, the shortcomings and strengths in this process are disparate in the two countries, both struggle with aspects of labour market integration that are achieved in the respective other country. The literature is aware of several factors influencing the labour market integration outcome of migrants. However, there is no clarity on the relevance and influence potential of single factors depending on the specific conditions in the host country. One reason is that detailed case studies considering diverse influencing factors within a holistic approach and also giving weight to the experiences of the concerned persons themselves - the refugees - are missing. With the help of an ethnographic approach, the present thesis shows that bureaucracy and institutional support, skills and experiences, as well as social networks, are the main drivers on the way into employment for refugees in Germany and Turkey. Yet, due to different national contexts, the degree and the way in which these factors shape the labour market entry diverges. While on the rather inflexible German labour market language skills are decisive and official certificates required to enter a job, social networks and the demonstration of practical skills are pivotal for employment on the Turkish labour market. Moreover, in Germany, high levels of bureaucracy and institutional support lead to a slow but eventually stable labour market integration of refugees. In Turkey, on the other hand, low levels of bureaucracy and institutional support push refugees into employment quickly but result in informal, unstable working situations. The results demonstrate that there is vast need and scope for improvement of labour market integration in both destinations by learning from already successful approaches adopted in the respective other country.

En fazla sayıda Suriyeli mülteciye ev sahipliği yapan iki Avrupa ülkesi olan Almanya ve Türkiye, bu mültecileri uzun vadede işgücü piyasalarına katılımı zorluğu ile karşı karşıya kalmaktadır. Bununla birlikte, iş gücü katılımıyla mücadele eden her iki ülkede de bu süreçteki zaaflar ve güçlü yönler farklıdır. Literatürde, göçmenlerin işgücü katılımını etkileyen birçok faktör belirtilmiştir. Ancak, ev sahibi ülkedeki özel koşullara bağlı olarak bir tek faktörün ilgisi ve etkisi konusunda net olunamaz. Bunun nedenlerinden biri, bütünsel bir yaklaşım içinde, farklı etkileyici faktörleri göz önünde bulunduran ve ayrıca mültecilerin kendi deneyimlerine ağırlık veren detaylı vaka çalışmalarının eksik olmasıdır. Etnografik bir yaklaşımın yardımıyla, bu araştırma; Almanya ve Türkiye'deki mültecilerin istihdamı için, bürokrasi ile kurumsal desteğin ve kabiliyet ile deneyimlerin yanı sıra sosyal bağlantıların da itici güç olduğunu göstermektedir. Bununla birlikte, ulusal şartların farklılığı nedeni ile bu faktörlerin işgücüne katılımı nasıl etkilediği ve etki dereceleri farklılaşmaktadır. Esnek olmayan Alman işgücü piyasası için dil becerileri ve resmi prosedürler belirleyici iken, Türkiye işgücü piyasasında istihdam için de sosyal bağlantılar ve yetenekler çok önemlidir. Üstelik Almanya‘daki yüksek düzeyde bürokrasi ve kurumsallık, mültecilerin yavaş ama sonuçta istikrarlı bir işgücü katılımına yol açarken, Türkiye'de mültecileri hızlı bir şekilde istihdam eden düşük düzeydeki bürokrasi ve kurumsallık, gayri resmi ve dengesiz çalışma durumlarına neden olmaktadır. Sonuçlar, geniş bir ihtiyaç kapsamında, iki ülke birbirlerinin başarılı yaklaşımlarını öğrenerek, işgücü piyasasına katılımın iyileştirilmesine yönelik gelişme sağlayabileceklerini göstermektedir.
Mültecilerden çalışanlara: Türkiye ve Almanya'daki Suriyeli mültecilerin işgücü piyasası entegrasyonunun karşılaştırılması